Fear and Coping with Death in Intensive Care Nurses: a Structural Model Predictor of Compassion Fatigue - Medina-Fernández, Josué; Torres-Soto, Nissa Yaing; Casco-Gallardo, Karina; Ruiz-Lara, Anahí; Martínez-Ramírez, Beatriz; Fuentes-Fernández, Esmeralda (Investigación y Educación en Enfermería, 2023)
Objective. To determine the effect of fear and coping with death on compassion fatigue in nurses working in the intensive care unit. Methods. Correlational-predictive design, applied in 245 nurses working in the intensive care unit through intentional sampling. The study applied a personal data card, the Collet-Lester Fear of Death Scale (α=0.72), the Bugen Fell of Death Scale (α=0.82), and the Empathy Exhaustion Scale (α=0.80). Descriptive and inferential statistics were performed, such as Spearman's test and a structural equation model. Results. The work had 255 nurses who participated, finding a relationship among fear and coping toward death and compassion fatigue (p<0.01), together with the equation model showing that fear and coping toward death have a positive effect in 43.6% on compassion fatigue. Conclusion. Fear and coping with death have an effect on compassion fatigue in nurses working in the intensive care unit, so that when working in a critical area it can cause health effects